The contemporary design of endovascular aneurysm stent-graft materials: PTFE versus polyester - Hynes, Niamh; Acharya, Yogesh; Sultan, Sherif (Frontiers in Surgery, 2022)
Endovascular aneurysm repair of the abdominal aorta (EVAR) and of the thoracic aorta (TEVAR) have revolutionised therapeutic strategies in the management of aortic pathology, and endovascular repair is now an established and attractive alternative to open surgical repair (OSR) due to its superior short-term safety profile. However, opinions are divided regarding its long-term cost-effectiveness, which is reflected in the controversial NICE guidelines on abdominal aortic aneurysm (AAA) repair published in 2018, which advised against EVAR for elective aortic repair due to high secondary intervention rates and resultant associated costs. There is no doubt that OSR continues to have a valuable role to play in aortic repair, but it is not universally applicable, especially in older and sicker patients. Therefore, we should not dismiss EVAR and TEVAR without examining the reasons for long-term failure, and the most obvious starting point is stent graft material properties. Polytetrafluoroethylene (PTFE) and polyester are the two most common stent-graft materials; however, there has been no objective comparison of PTFE and polyester stent-graft post-procedural outcomes in EVAR and TEVAR, or even OSR. This lack of definitive data on different stent-graft materials and their configuration necessitates a comprehensive review to elucidate the post-procedural outcome in terms of endograft failure, cardiovascular events, and aortic-related mortality and morbidity